Indigenous Women’s Politics of Care: Human and medicinal plants vital connections in the Caititu Land, Brazilian Amazon - Markus S. Enk; Luciana Kind (Archivio Antropologico Mediterraneo)
In this paper we describe the establishment of medicinal plantbeds as part of the Takatxi Nhipukutximyna project in the Caititu Indigenous Land, located in the Purus Region of the Brazilian Amazon. Based on an ethnographic and narrative research conducted between 2023 and 2024, it examines how indigenous women’s practices with medicinal plants challenge anthropocentric paradigms of health while reclaiming an indigenous way of living. We describe how plants like rue (arruda) reciprocate human care by offering protection and healing of the human and plant communities. The human-plant alliance sustains the interdependence between human and plant well-being by engaging with owners-of-nature - beings that protect the environment and its inhabitants. Based on our research’s post-colonial setting, we suggest intersectionality and indigenous perspectives to provide novel understandings of multispecies frameworks of relational health.